1979
DOI: 10.1111/j.1365-2338.1979.tb02242.x
|View full text |Cite
|
Sign up to set email alerts
|

A Concept of Pest Risk Analysis

Abstract: A pest risk analysis curve on a graph is used to present diagramatically 1) the concept of pest risk analysis, and 2) the interaction of biological, economical, social, and political factors with quarantine policies, regulations, or decisions. The culmination of these regulatory activities often leads to a decision about the entry status of a wide spectrum of imported “items”. While the concept pertains to animal as well as plant quarantine matters, this paper concentrates on plant quarantine. Most of the exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…After the pests to be excluded have been targeted by the pest risk evaluation for a particular type of plant material, decisions must be made concerning what regulatory actions will be taken on the plant material. If biological factors are used to determine the extent of regulation, there should be a direct relationship between the risk of entry and establishment by the pest and the severity of the regulation for potentially contaminated plant material (29). However, if other factors such as economics or politics influence regulatory decisions, it may not be obvious from an evaluation of biological factors why certain regulatory actions are taken with particular types of plant material.…”
Section: Purpose Of Regulatory Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…After the pests to be excluded have been targeted by the pest risk evaluation for a particular type of plant material, decisions must be made concerning what regulatory actions will be taken on the plant material. If biological factors are used to determine the extent of regulation, there should be a direct relationship between the risk of entry and establishment by the pest and the severity of the regulation for potentially contaminated plant material (29). However, if other factors such as economics or politics influence regulatory decisions, it may not be obvious from an evaluation of biological factors why certain regulatory actions are taken with particular types of plant material.…”
Section: Purpose Of Regulatory Activitiesmentioning
confidence: 99%
“…In this discussion, the terms " regulatory action" and " safeguard" refer to a condition of entry designed to exclude pests, in an active manner, as implied by the first term, or in a protective manner, as suggested by the second term. In fact, the regulation of a particular type of plant material is usually a combination of two or more regulatory actions or safeguards (29). The hope is that each appropriate safeguard will further reduce the probability that the undesirable pest will enter and become established in the domestic agriculture.…”
Section: Regulatory Actionsmentioning
confidence: 99%
“…A review by the author of the scientific literature on submicroscopic pathogens which infect grasses revealed that 80-100 of these pathogens may be of quarantine significance to the United States. Indexing of some grass introductions from Africa and Australia by the author at the PQF has resulted in thehetection of pathogens of quarantine significance (Kahn et al, 1979).…”
Section: B Grassesmentioning
confidence: 99%
“…One of the goals in APHIS is to develop plant quarantine laws and procedures which are biologically defensible. The severity of the quarantine action against any type of plant material should be directly correlated with the risk that this plant material may be carrying one or more pests of quarantine significance (Kahn, 1979). Pest risk is evaluated by reviewing the scientific literature and exchanging information with foreign plant protection oficials concerning the damage and dissemination of exotic pests.…”
Section: Introductionmentioning
confidence: 99%